Quality engineering in production systems - Taguchi, Genichi; Elsayed, Elsayed A.; Hsiang , Thomas C. (New York: McGraw-Hill, 1989)
This book is intended primarily for those involved in the research, development, and manufacturing phases of a product's life-cycle, including design engineers, production and manufacturing engineers, quality engineers and applied statisticians. It is also intended for senior undergraduate students and first year graduate students in industrial, production, manufacturing and systems engineering disciplines. The purpose was to give the students a familiarity with basic statistical quality control. Examples are provided throughout the book to reinforce and illustrate the concepts, methods and approaches involved. The end of each chapter contains problems to facilitate practice.
1.Quality value and engineering -- 2.Loss function and quality level -- 3.tolerance design and tolerancing -- 4.On-Line feedback quality control:variable Characteristics -- 5.On-Line process Parameter control:variable characteristics -- 6.On-Line quality control: attribute Characteristics -- 7.On-Line quality control:Methods for process improvements -- 8.Introduction to preventive Maintenance
Pages from 70-73 are missing.
Includes index
Keywords: Quality Control -- Statistical Methods; Production Management -- Quality Control